Production of HPC-based extrudates by hot-melt extrusion - Marôvas, Inês Filipa Rocha (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014